VALUE ADDED GREEN BEANS INTO GREEN BEAN BREAD CAP RAJAWALI IN TEBING TINGGI - Ragnar Octavianus Sitorus; Medi Lilis Wenny Nainggolan (ITScience (Information Technology and Science), 2022)
This study aims to find out how to process Cap Rajawali mung bean bread, find out the added value of the Rajawali brand mung bean bread processing business, find out the income of Cap Rajawali Bread and determine the feasibility level of Cap Rajawali mung bean bread processing business. Determination of the research area is done purposively. The method of determining the processing sample is the census method. The study results found that the stages of processing mung beans into mung bean bread with stamp Rajawali started from the provision of raw materials, grinding raw mung beans that were still round into halves, soaking mung beans, draining mung beans, boiling mung beans, milling mung beans, mixing beans, green bean bread dough, making tausa as a filling for opaque skin, roasting mung bean bread, and packaging mung bean bread with Rajawali stamp. The added value of processing mung beans into mung bean bread stamped Rajawali is 71.13%, meaning that the added value of processing mung beans into mung bean bread stamped Rajawali is quite high. The income earned is Rp. 331,137,592.30, which means that the income of entrepreneurs (processors) of mung bean bread Cap Rajawali is high. The processing business of mung bean stamped Rajawali has an R/C of 2.54 (Easy to Work); for mung bean bread with the label Rajawali in small boxes, the production is 13,200 boxes > BEP for small box production is 5,054 boxes, and the price is Rp. 25,000 > BEP for the price of a small box is Rp. 9,571.14. For mung bean bread with Rajawali stamp in large boxes, the production is 7,200 boxes > BEP for large box production is 2,951 boxes, and the price is Rp. 30,000 > BEP, the price for large boxes is Rp. 12,294.90. This study concluded that processing mung beans into mung bean bread with stamp Rajawali is feasible in the research area.